Nipah virus Infection: A fatal Emerging disease - Islam, Mirza Md Ziaul; Rahman, M Mizanur (Northern International Medical College Journal, 2016)
Abstract not available Northern International Medical College Journal Vol.7(2) Jan 2016: 146-148